Exploring the Impact of Online Education on Higher Education - Kamraju, M.; Krishnaiah, J.; Durgesham, G.; Shaba, Noor; Begum, Syeda Akhtar; Fatima, Nazneen; Madhuri, Y. (Bumi Publikasi Nusantara, 2024)
The increasing popularity of online education has led to a significant shift in the way higher education is delivered. This study aims to explore the impact of online education on higher education by examining its benefits and challenges. A qualitative research approach was employed to collect data from instructors and students who have experienced online education. Semi-structured interviews were used to gather data, which was analyzed using thematic analysis. The findings of the study suggest that online education has a positive impact on higher education in terms of accessibility, flexibility, and convenience. Online education provides opportunities for students to access educational resources from anywhere at any time and at their own pace. It also allows students to balance their academic and personal commitments more effectively. However, challenges such as lack of social interaction, technical issues, and self-discipline were identified as barriers to effective online education. The study highlights the importance of designing online courses that promote interaction, engagement, and collaboration among students and between students and instructors. It also emphasizes the need for providing adequate support and training to instructors to ensure the effective delivery of online education. Overall, the study concludes that online education has the potential to enhance the quality of higher education by providing opportunities for lifelong learning and professional development.